2019
DOI: 10.3847/2041-8213/ab222e
|View full text |Cite
|
Sign up to set email alerts
|

Active Galactic Nuclei in Dusty Starbursts at z = 2: Feedback Still to Kick in

Abstract: We investigate a sample of 152 dusty sources at 1.5 < z < 2.5 to understand the connection of enhanced Star-Formation-Rate (SFR) and Black-Hole-Accretion-Rate (BHAR). The sources are Herschel-selected, having stellar masses M * > 10 10 M and SFR (∼ 100 − 1000M /yr) elevated (> 4×) above the star-forming "main sequence", classifying them as Starbursts (SB). Through a multiwavelength fitting approach (including a dusty torus component), we divided the sample into active SBs (dominated by an AGN emission, SBs-AGN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…starbursts) are even more efficient at triggering AGNs. Similar to our results, Rodighiero et al (2019) find higher BHARs in starbursts, with a factor of 3 enhancement compared to normal star-forming galaxies for a sample of 1.5<z<2.5 galaxies with a great diversity of star-forming properties. In their Figure 3, they present predictions of an enhancement of BHAR and BHAR/SFR during the merger phase based on the hydrodynamical models of Di and Hopkins et al (2012), which is in agreement with our findings (see Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…starbursts) are even more efficient at triggering AGNs. Similar to our results, Rodighiero et al (2019) find higher BHARs in starbursts, with a factor of 3 enhancement compared to normal star-forming galaxies for a sample of 1.5<z<2.5 galaxies with a great diversity of star-forming properties. In their Figure 3, they present predictions of an enhancement of BHAR and BHAR/SFR during the merger phase based on the hydrodynamical models of Di and Hopkins et al (2012), which is in agreement with our findings (see Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…Despite the large scatter of one order of magnitude or more among different studies, the H 2 mass density parameter Ω H 2 is observed to increase at z ≃ 0-3, assembling its mass with almost no observed environmental dependence (Darvish et al 2018;Tadaki et al 2019;Garratt et al 2021), and has been found to mimic the cosmological star formation rate (SFR) density at higher z (Decarli et al 2020;Riechers et al 2020a). These observations highlight the longstanding need to explore the origin of the large supply of H 2 gas required to sustain star formation at different z (Rodighiero et al 2019;Tacconi et al 2020;Hunt et al 2020) and question the ability to explain the large H 2 fractions (above 50%) detected in galaxies around z ∼ 4-6 (Dessauges-Zavadsky et al 2020;Boogaard et al 2021) in a primordial, presumably metal-poor gas. From a theoretical point of view, cold gas plays a key role in cooling and fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…This picture might suggest that just like the majority of galaxies follow a main-sequence in the SFR-M * plane, a similar relation between the black hole accretion rate (BHAR) and the M * might exist: the more massive the galaxy, the higher the availability of inflowing gas for star formation and black hole accretion, which would mean that they both should correlate with stellar mass. In addition, galaxies offset from the mainsequence (starbursts and quiescents), might have a BHAR that varies accordingly with the gas that is typically available in that phase (Rodighiero et al 2019).…”
Section: Introductionmentioning
confidence: 99%